Association Between Sterilization Governance and Perceived Productivity Among Healthcare Facilities in Tuguegarao City, Philippines - Felixberto Gacias; Estarlita Gomba-Dela Cruz; Marmelo Abante (Research Synergy Foundation, 2026)
Sterilization of reusable medical devices (RMDs) is central to infection prevention and healthcare quality, yet limited empirical evidence links sterilization governance to perceived productivity outcomes in provincial health systems. This quantitative investigation examined the association between sterilization practices and perceived healthcare provider productivity in Tuguegarao City, Philippines, and explored implications for outsourcing readiness and centralized planning. A cross-sectional survey was conducted among 189 healthcare professionals across hospitals, dental clinics, and ambulatory facilities. The adapted instrument underwent formal Content Validity Index (CVI) evaluation by a seven-member multidisciplinary expert panel (S-CVI/Ave = 0.91), demonstrating excellent content validity. Perceptions across eight sterilization domains were measured using structured four-point Likert-scale items. Descriptive statistics, Mann-Whitney U tests, and Spearman's rank-order correlation were applied. Technical compliance domains demonstrated uniformly high agreement with no significant group differences (p = 1.000). Significant differences emerged in coordination-related domains—process standardization, customer service, sterile storage and distribution, and education and training (p < 0.001; r = 0.86). A perfect positive monotonic association was identified between perceived sterilization practices and perceived productivity (rho = 1.000). Given the bounded ordinal scale and ceiling effects, this likely reflects perceptual alignment rather than independent construct variability. Findings suggest governance refinement should prioritize coordination mechanisms and service-level clarity rather than core technical compliance. The study introduces the Gacias Sterilization Systems Intelligence Framework (G-SSIF) to guide outsourcing readiness in resource-variable healthcare systems.